PENGADAAN BERAS KUALITAS MEDIUM DI PERUM BULOG SUB DIVISI REGIONAL SURABAYA UTARA - Ramadhani, Faradillah Intan; agridevina, Sudiyarto; agridevina, Sumartono (Berkala Ilmiah AGRIDEVINA, 2016)
Rice is one of the most strategic food from various food types(principal) in Indonesia. In order to meet the needs of thesupply of rice, BULOG procuring or purchasing grain and ricefrom farmers. However, the rice procurement target medium inPerum BULOGSub Regional Division North Surabayais not inaccordance with the results of the procurement in the field.This study aimed to analyze the mechanism of procurement ofmedium rice byPerum BULOG Sub Regional Division NorthSurabaya, the actual provision of medium rice in terms ofquantum and the duration from procurement to distribution, aswell as the perceptions of employees, inspectors quality andPartnersProcurement(MKP)aboutchangesinimplementation of medium ricequality checks on procurement.The data used consist of primary and secondary data withqualitative descriptive analysis. From the analysis it can beconcluded that: (1) procurement mechanism begins withdetermining the procurement target of Directors or to anyDivision Regional Centre. Further targeting of Head ofRegional Division for each Sub Regional Division. SubRegionalDivisionastheimplementingoperationalprocurement activities. (2) Actual procurement of medium ricein 2015 amounted to 138.116 tons and distribution of 224.961tons. Procurement in 2016 amounted to 105.273 tons anddistribution of 265.475,5 tons. (3) According to employees, thedifference between the inspection of medium quality rice in theprocurement of the old and the new one is in terms of location.There is no loss of any change in the implementation of qualityinspection, but there are some advantages. According to theinspector of quality, the difference between the inspection ofmedium quality rice in the procurement of the old and the newis the place to check. There is no loss of any change in theimplementation of quality inspection, but there are someadvantages. According Partners Procurement (MKP), thedifference between the inspection of medium quality rice in theprocurement of the old and the new isthe location forexamination. There is no benefit from a change in theimplementation of quality inspection, but there are someadvantages.Key words: Procurement, Medium Rice,Perum BULOGSubRegional Division North Surabaya